Analysis of the Utilization of Science Laboratories in Integrated Islamic Junior High Schools - Ulfah 'Aini; M Rahmad; Niken Indrata Marselina; Arfy Masyhuri; Doriani Doriani; Roza Linda (PSEJ (Pancasakti Science Education Journal), 2025)
This research was conducted to examine the management of the science laboratory at Al Fityah Integrated Islamic Junior High School Pekanbaru, which has not been optimal, thereby hindering the effectiveness of practical-based learning. The research aims to describe and analyze science laboratory management based on four management aspects: (1) planning, (2) organizing, (3) implementation, and (4) monitoring and evaluation. This study uses a descriptive research method with a case study approach. The research subjects include eighth-grade students, the school principal, the laboratory head, and science teachers. Data was collected through observation, interviews, documentation, and questionnaires. Data analysis followed the Miles and Huberman model (data reduction, data presentation, and conclusion drawing) with source triangulation to ensure validity. The results indicate that: (1) Laboratory management planning is not systematic—there are no SOPs, work programs, or written practical schedules; (2) Organization does not follow management principles—the organizational structure is informal, with the laboratory head also serving as a teacher without laboratory staff support; (3) Implementation is suboptimal—practicals are rarely conducted in the laboratory (mostly in classrooms), equipment is limited, and there are no occupational health and safety (OHS) procedures; (4) Monitoring and evaluation are informal, lacking documentation or external supervision. Based on the findings, the science laboratory management in this school does not meet the standards, primarily due to weaknesses in the management system across all four aspects. Therefore, comprehensive improvements are needed to support practical-based science learning in the laboratory.